Association of Abnormal Serum Copper and Zinc Levels with Psoriasis Severity - Bibi Hajira Ishaq, Muhammad Hanif, Obaid ur Rahman, Zafar Ahmed Khan, Shaista Alam, Tehseen Naveed, Zahoor Ahmed, Shabir Ahmad Orakzai, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Psoriasis is a chronic, recurring inflammatory skin disease characterized by red, scaly patches that can cause considerable discomfort and affect the patient's daily life. This study aims to reveal abnormalities in psoriasis patient serum copper and zinc levels. Materials and Methods: This cross-sectional study was conducted in District Headquarters Hospital Nowshehra from February 2021 to February 2023. Two hundred fifty participants with psoriasis were enrolled. Data was collected from the demographic information of each participant, including age, sex, and clinical history. Peripheral blood samples were collected from the participants in the fasting state after an overnight fast and centrifuged at 3000rpm to extract the serum. Serum concentrations of copper and zinc were measured using standardized laboratory procedures. Results: The study included two hundred fifty patients of both genders. The mean age was 42.98±8.01 years for the psoriasis group and 40.01±7.23 years for the healthy control group. Regarding gender distribution, 60% of psoriasis patients and 52% of healthy controls were male. Patients with psoriasis showed elevated serum copper levels (120 ± 15 μg/dL) compared to healthy controls (110 ± 12 μg/dL) (p<0.001). Conversely, their serum zinc levels were lower (90 ± 10 μg/dL) compared to healthy controls (100 ± 8 μg/dL) (p<0.001). Study Findings: Our study reveals an alarming level of serum copper and zinc concentration deviation among psoriasis patients, which signifies a possible disturbance of trace metal equilibrium in the body due to psoriasis. Keywords: Psoriasis, Serum copper, Serum zinc, Trace metal imbalance, Psoriasis severity